Whole Exome Sequencing in the Diagnosis of Children with Suspected Neurometabolic Diseases Attending a Tertiary Care Hospital of Bangladesh (Bangladesh Journal of Medicine, 2026)
Background: Neurometabolic disorders (NMD) encompass rare genetic errors affecting metabolism, often with neurological consequences. These disorders, characterized by genetic defects impacting enzyme function or vitamin deficiencies, can lead to severe neurological symptoms and lifelong disability. Whole exome sequencing (WES) is a vital diagnostic tool, offering a high yield in identifying genetic causes, especially in cases where traditional screenings fail to achieve diagnostic confirmation. Diagnostic confirmation is essential for providing precise treatment, genetic counseling, and prevention strategies for neurometabolic disorders. This study was conducted with the aim to observe the genetic profile of suspected neurometabolic diseases in children by whole exome sequencing.Method: The study was conducted at the department of pediatric neurology at the Institute of Pediatric Neurodisorder and Autism (IPNA) of Bangladesh Medical University (BMU) from April 2024 to March 2025, focused on infants and children suspected of neurometabolic diseases. Those aged over 1 month to less than 18 years with inconclusive initial metabolic screenings underwent whole exome sequencing for diagnosis. Real-world data were used, with subjects enrolled through convenience sampling with parental consent. The study adhered to the Ethical Committee's approval at Bangladesh Medical University. Detailed assessments included history taking, physical examinations, and investigations, with WES reports classified following ACMG guidelines.Results: In this study of 21 patients, with a gender distribution of 66.7% male and 33.3% female, consanguinity was present in 47.6% of cases. Common clinical features encompassed developmental delays, seizures, developmental regression. Basic metabolic screenings and neuroimaging unveiled specific abnormalities. Whole exome sequencing identified various gene mutations and neurometabolic diseases, including glycine encephalopathy, phenylketonuria and developmental and epileptic encephalopathies.Conclusion: This research demonstrated, whole exome sequencing (WES) provided valuable diagnostic information regarding different types of neurometabolic diseases in suspected children with neurometabolic diseases.Bangladesh J Medicine 2026; 37(2): 106-113